Capturing intensive horticulture activities in Lower Nyando, Kenya - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) East African regional program has selected six sites to test interventions that address risks related to climate change and variability. The ambition is to help farmers find new and improved farming techniques and agricultural knowledge that will help them adapt to climate change while reducing related emissions, and strengthen their livelihoods at the same time. In these photos, from Lower Nyando Kenya, farmers (who are members of a youth group) tend to tomatoes and other vegetables in their farm. Photos: K. Trautmann. Please credit accordingly.